Sububjectivity and Response Behaviors of Flood-affected People during the 2011 Mega Flood Crisis - Chomsri, Jiraporn; Sherer, Penchan (The Journal of Behavioral Science, 2013)
The study explored the subjectivity of flood-affected people and behavioral response to the 2011 mega flood crisis in Thailand. The study used a qualitative approach, conducted with ten flood-affected people in a community located in Phra Nakhon Si Ayutthaya Province of Thailand. Data was collected through in-depth interviews, observations, and documentary review and examined by content analysis. The results of content analysis revealed subjectivity reflected in the feelings and actions of flood-affected people. These participants originally perceived flooding as a natural phenomenon and believed it to be normative. Subjectivity was influenced by local knowledge based on prior flood experiences, which were significant factors for response behavior during the flood crisis. Flood-affected people assumed the flood situation was controlled and prepared to live with flooding by buying food, constructing levees, and moving belongings within their home, but the flood situation became uncontrollable; the situation was beyond their expectations and generated subjectivity that this was a man-made phenomenon related to poor water management and environmental degradation. Coping behaviors related to seeking shelter depended on proximity and the social networks of individuals. Recommendations for future flood response include collective behavior rather than individual response and integration of local knowledge in standard warning systems. The recommendations generated by this study were derived from subjectivity and behavioral response, which rely on social contexts. It was suggested that local knowledge should be integrated for disaster management with advanced local management, like monitoring systems, and aid social network systems.